2020
DOI: 10.1175/jhm-d-20-0033.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Radar Quantitative Precipitation Estimates (QPEs) as an Input of Hydrological Models for Hydrometeorological Applications

Abstract: Weather radar provides real-time, spatially distributed precipitation estimates, whereas traditional gauge data are restricted in space. The use of radar quantitative precipitation estimates (QPEs) as an input of hydrological models for hydrometeorological applications has increased with the development of weather radar worldwide. New dual-polarization technology and algorithms are showing improvements to radar QPEs. This study evaluates radar QPEs from C-band radar at King City, Canada (WKR), and NEXRAD S-ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 77 publications
(90 reference statements)
0
16
0
1
Order By: Relevance
“…Recent progress and changes in weather radar hydrologic applications make its use a crucial tool for water resource management. The main topics of growth concerning weather radar applied to hydrology related to: (i) radar QPE [42][43][44][45][46], (ii) multi-radar and multi-sensor precipitation analysis [47][48][49], (iii) hydrologic modelling [50][51][52], (iv) urban hydrologic and hydraulic applications [48,[53][54][55][56], (v) precipitation frequency analysis [57,58], (vi) hydrometeorological process studies [59,60], (vii) precipitation nowcasting, forecasting [61], (viii) hydrometeorological applications [62].…”
Section: Hydrologic Applications Of Weather Radarmentioning
confidence: 99%
“…Recent progress and changes in weather radar hydrologic applications make its use a crucial tool for water resource management. The main topics of growth concerning weather radar applied to hydrology related to: (i) radar QPE [42][43][44][45][46], (ii) multi-radar and multi-sensor precipitation analysis [47][48][49], (iii) hydrologic modelling [50][51][52], (iv) urban hydrologic and hydraulic applications [48,[53][54][55][56], (v) precipitation frequency analysis [57,58], (vi) hydrometeorological process studies [59,60], (vii) precipitation nowcasting, forecasting [61], (viii) hydrometeorological applications [62].…”
Section: Hydrologic Applications Of Weather Radarmentioning
confidence: 99%
“…It is assumed that TRCA rain gauges characterize the precipitation distribution over the entire watershed. This assumption is valid due to the relatively small size of the watershed and relatively high rain gauge density of one gauge per ;75 km 2 (Wijayarathne et al 2020b). Subhourly (5-15 min) streamflow data from 2013 to 2018 recorded by the Water Survey of Canada (compiled at https://wateroffice.ec.gc.ca/search/historical_ e.html) were collected from a long-term flow gauge named ''Islington'' (identifier: 02HC033) (Fig.…”
Section: Study Areamentioning
confidence: 99%
“…In Canada, research in weather radar began after the Second World War in 1943 under the project Stormy Weather (Sills and Joe 2019;Douglas 1990). Weather radars were subsequently used for various hydrological studies in the Canadian context (Wijayarathne et al 2020a;Hassan et al 2019;Sills and Joe 2019;Huang et al 2010;Hudak et al 2008Hudak et al , 2002Brown et al 2007;Chen and Farrar 2007;Germann and Zawadzki 2004;Germann and Zawadzki 2002;Bellon and Zawadzki 1994;Bellon andAustin 1984, 1978;Bellon et al 1980;Barge et al 1979). The main applications of weather radar in Canada include determining the type of precipitation, precipitation features, and structure, operational forecasting such as weather forecasts and snow depth predictions, operational weather warnings, and as a tool to validate atmospheric models (Sills and Joe 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Paixao et al [7] suggested the simultaneous use of remotely sensed radar observations and tipping bucket rain gauges recording, to better identify areas with homogeneous severe precipitation. The effectiveness of radar quantitative precipitation estimates (QPEs) for the assessment of reliable rainfall intensity to be used to hydrological software was also punctuated by Wijayarathne et al [8].…”
Section: Introductionmentioning
confidence: 99%